1990
DOI: 10.1037/0096-1523.16.1.135
|View full text |Cite
|
Sign up to set email alerts
|

On the locus of visual selection: Evidence from focused attention tasks.

Abstract: Early and late selection models of attention disagree about whether visual objects are identified before or after selection, with recent evidence of interference from to-be-ignored stimuli favoring late selection over early selection accounts. However, these tests may not have permitted optimal attentional focusing. In 4 experiments subjects identified an attentionally cued target letter embedded among distractors. Only minimal effects of information appearing in to-be-ignored locations were observed. This str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

37
355
4
5

Year Published

1993
1993
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 279 publications
(401 citation statements)
references
References 48 publications
(87 reference statements)
37
355
4
5
Order By: Relevance
“…We highlight that our behavioural and electrophysiological data for the visual target detection task provide evidence that our paradigm manipulation was effective. Specifically, participants performed worse during the high load condition and P300 mean amplitude was significantly larger for low load blocks, consistent with what our expectations (e.g., Dark, Johnston, Myles-Worsley, & Farah, 1985;Kok, 2001;Polich, 1987;Yantis & Johnston, 1990). Given that the capacity and distribution of attention resources are known to change with age (e.g., Craik & Byrd, 1982), future work regarding how attention is allocated to task-irrelevant peripheral probes in older adults is warranted.…”
Section: Additional Issuessupporting
confidence: 84%
“…We highlight that our behavioural and electrophysiological data for the visual target detection task provide evidence that our paradigm manipulation was effective. Specifically, participants performed worse during the high load condition and P300 mean amplitude was significantly larger for low load blocks, consistent with what our expectations (e.g., Dark, Johnston, Myles-Worsley, & Farah, 1985;Kok, 2001;Polich, 1987;Yantis & Johnston, 1990). Given that the capacity and distribution of attention resources are known to change with age (e.g., Craik & Byrd, 1982), future work regarding how attention is allocated to task-irrelevant peripheral probes in older adults is warranted.…”
Section: Additional Issuessupporting
confidence: 84%
“…Second, there was a reliable increase in the magnitude of negative priming from ignored distractors when the prime target location was precued. This result is inconsistent with the conclusion that precuing target location prevents the semantic analysis of spatially separate distracting information (see Paquet & Lortie, 1990;Yantis & Johnston, 1990).…”
Section: Discussioncontrasting
confidence: 60%
“…To illustrate, if reduced interference with increasing target-distractor separation is due to less activation of the distant distractors (e.g., Kahneman & Henik, 1981), then neither interference nor negative priming would be expected from distant distractors if the target location was validly precued. Several studies have shown that precuing target location does indeed reduce or eliminate interference from response-incompatible distractors (Paquet & Lortie, 1990;Yantis & Johnston, 1990). However, a series ofexperiments reported by Fox (in press), demonstrated that although precuing target location does indeed reduce the magnitude of interference effects, the magnitude of negative priming does not decrease in precued relative to uncued trials.…”
Section: Resultsmentioning
confidence: 99%
“…It consists of experiments performed to study the extent to which nontarget stimuli are processed along with the target stimulus. In a number of these experiments (e.g., those of LaBerge & Brown, 1986;Miller, 1991;Yantis & Johnston, 1990), researchers have employed the responsecompetition paradigm introduced by C. W. Eriksen and Hoffman (1973) and B. A. Eriksen and C. W. .…”
mentioning
confidence: 99%
“…W. Eriksen & St. James, 1986;Miller, 1991;Yantis & Johnston, 1990). If sufficient time in the form of a location precue is provided, incompatible noise stimuli located beyond about ATTENTIONAL DISTRIBUTION 135 a degree of visual angle from the target are found to have no measurable effect (c. W. Eriksen and Hoffman, 1973;.…”
mentioning
confidence: 99%